The effectiveness of the use of various types of fertilizers and methods of their application in the cultivation of watermelon - E. A. Galichkina; M. V. Bykova; S. M. Nadezhkin; N. V. Tsirulnikova (Овощи России, 2021)
Relevance. The Volgograd region has a number of factors necessary for the cultivation of melons and gourds. The development of new varieties and hybrids of watermelon should involve the development of varietal agricultural techniques that would allow realizing the genetic potential of the variety. Therefore, the development of new methods of cultivation technologies that allow obtaining guaranteed fruit yields without reducing the quality of table watermelon products in the dry-steppe Trans-Volga region is relevant and timely.Material and methodology. The object of research is a watermelon, cultivar Zemlyanin. New types of water-soluble fertilizers – B and Fe chelates, and the Vegetable Akvarin were studied, by using them for soaking seeds before sowing and processing plants during the growing season.Results. The use of chelates B and Fe in the technology of growing watermelon, as well as the Akvarin, is an effective method for obtaining guaranteed yields. The use of water-soluble fertilizers, with various methods of their use, provided an increase in the yield of watermelon by 1.6-8.3 t/ha, or by 6.9-35.9% in comparison with the control (option without treatments). The largest fruits were obtained in variants of chelate B and the Vegetable Akvarin (processing of plants) – 6.8 kg. Comparative analysis of the biochemical composition of the fruits showed that water-soluble chelated fertilizers do not have a negative effect on the accumulation of nitrates. Studies have revealed the positive effect of water-soluble micronutrient fertilizers on improving the quality of fruits, which was manifested in the growth of the content of vitamin C and sugars.